Changes in beliefs about language learning among Chinese EAP learners in an EMI context in Mainland China: A socio-cultural perspective. (December 2015) - Li, Chili; Ruan, Zhoulin
Abstract: This paper reports on a longitudinal study of changes in beliefs among Chinese EAP learners during a transitional period at an EMI university in Mainland China. Data were collected through questionnaires and semi-structured interviews, which were administered at two phases over one academic year. The study revealed significant changes in the learner beliefs after they studied EAP for an academic year at the EMI University. The changes were found to arise from the mediation of an array of socio-cultural factors in the EMI setting, which include content subjects taught in English, extracurricular activities, formative assessments, and important others such as teachers. The study illuminates the nature of learner beliefs as a socially situated construct, and has pedagogical implications for English language teaching in EMI contexts.